1972
DOI: 10.1104/pp.49.5.725
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Nitrate Reductase in Leaves of Prunus Species

Abstract: Nitrate reductase was found in leaves of apricot Prunus armeniaca, sour cherry P. cerasus, sweet cherry P. avium, and plum P. domestica, but not in peach P. persica, from Grasmanis and Nicholas (8) extracted an active nitrate reductase from apple roots, but they were unable to determine its physiological electron donor. Then Klepper and Hageman (11), employing insoluble PVPW in the extraction medium, obtained a typical NADH-dependent nitrate reductase from apple roots. Adding excess nitrate ions to the root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…to foliar nitrate sprays under field conditions (Leece and Kenworthy 1971) is not caused by an inability of Prunusleaves to metabolize nitrate ions (Leece, Dilley, and Kenworthy 1972). This is analogous to the response ofPrunus spp.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…to foliar nitrate sprays under field conditions (Leece and Kenworthy 1971) is not caused by an inability of Prunusleaves to metabolize nitrate ions (Leece, Dilley, and Kenworthy 1972). This is analogous to the response ofPrunus spp.…”
mentioning
confidence: 74%
“…In an earlier study (Leece, Dilley, and Kenworthy 1972), nitrate uptake via the petiole was measured, using the nitrate reductase assay. In that system, steps (2), (3), and (4) were operating as above, but step (1) became petiole uptake, which was controlled by the rate of leaf transpiration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on both nitrate concentration in xylem sap exudates and in vivo and in vitro NRA showed that woody plants reduce their nitrate almost exclusively in the roots (Cruz et al, 1991(Cruz et al, , 1993Gojon et al, 1991;Lee and Titus, 1992;Thomas and Hilker, 2000). However, under high exogenous nitrate availability, NRA has also been detected in the leaves of woody plants (Klepper and Hageman, 1969;Leece et al, 1972;Smirnoff et al, 1984;Lee and Titus, 1992;Olsson and Falkengreen-Grerup, 2003). In addition to environmental factors, nitrate reduction also shows changes during organ and plant development (Andrews, 1986;Kenis et al, 1992).…”
Section: Introductionmentioning
confidence: 99%